Southern Rockies landscape conservation cooperative (SRLCC) - Colorado Natural Heritage Program, author (Colorado State University. Libraries, 2014)
Discusses the Southern Rockies Landscape Conservation Cooperative plan.
Presented at the Colorado Natural Heritage Program 2013-2014 Partners Meeting held on January 14, 1014 in the USGS Fort Collins Science Center, Building C, Fort Collins, Colorado.
Keywords: Colorado; conservation; environment; Rocky Mountains